Persistence of pentolite (PETN and TNT) in soil microcosms and microbial enrichment cultures (2016)
Pentolite is a mixture (1:1) of 2,4,6-trinitrotoluene (TNT) and pentaerythritol tetranitrate (PETN), and little is known about its fate in the environment. This study was aimed to determine the dissipation of pentolite in soils under laboratory conditions. Microcosm experiments conducted with two soils demonstrated that dissipation rate of PETN was significantly slower than that of TNT. Interestingly, the dissipation of PETN was enhanced by the presence of TNT, while PETN did not enhanced the dissipation of TNT. Pentolite dissipation rate was significantly faster under biostimulation treatment (addition of carbon source) in soil from the artificial wetland, while no such stimulation was observed in soil from detonation field. In addition, the dissipation rate of TNT and PETN in soil from artificial wetland under biostimulation was significantly faster than the equivalent abiotic control, although it seems that non-biological processes might also be important for the dissipation of TNT and PETN. Transformation of PETN was also slower during establishment of enrichment culture using pentolite as the sole nitrogen source. In addition, transformation of these explosives was gradually reduced and practically stopped after the forth cultures transfer (80 days). DGGE analysis of bacterial communities from these cultures indicates that all consortia were dominated by bacteria from the order Burkholderiales and Rhodanobacter. In conclusion, our results suggest that PETN might be more persistent than TNT. © 2016, Springer-Verlag Berlin Heidelberg.